Design and development of mini autonomous surface vessel for bathymetric survey - Mohd Adam, Muhammad Ammar; Zainal Abidin, Zulkifli; Ibrahim, Ahmad Imran; Mohd Ghani, Ahmad Shahril; Anchumukkil, Al Jawharah Anchumukkil (Springer, 2020)
Bathymetric survey is necessary in monitoring hydrographic environment. The conventional approach involves operators including engineer, surveyor and boat captain being onboard the vessel during survey works. Application of Autonomous Surface Vessel (ASV) is becoming popular for bathymetric mapping as it reduces operation cost and replaces human operation in high risk areas. Available commercial ASVs are typically designed for a particular task with limited expandability for other similar applications. Also, with current miniaturization of industrial sensors, a small-sized ASV is sufficient for most inland water survey operation. In this paper, the design and development components for a modular and mini ASV, named Suraya-1 is detailed. This vessel is developed for hydrographic survey using singlebeam depth sonar, measuring depth and temperature of a water body. The specifications and performance of developed ASV is compared to existing commercial unmanned vessels of same class and application. The dimension of the vehicle is the smallest compared to counterparts which is 1.04 m × 0.35 m × 0.32 m, weighing only 6.8 kg without payload. Our ASV is powered by two paralleled 18.5 V LiPo battery, which is in the mid-range, yet able to reach navigation speed of 4 knots as required for survey work. The real-time vessel poses and collected data are transmitted to the ground station within range of 2 km. For performance evaluation, the developed ASV is tested in pool environment. Qualitative outcome shows minimal error in navigation control. Also, output data obtained is shown consistent and reliable for a calm water environment.